(untitled) (Indonesian Journal of Counseling and Development, 2023)
In today’s world, there is a shift in student needs for guidance and counseling services in the era of Society 5.0. This study aims to uncover the implementation of the guidance and counseling program in public madrasah aliyah. The study employs qualitative research with a naturalistic approach, which describes the actual conditions without manipulation but is based on data obtained qualitatively through observation and interviews. The informants of the research are state Madrasah Aliyah teachers in the era of Society 5.0. The data analysis technique uses a pattern developed by Miles and Huberman. The findings suggest that the guidance and counseling program at state Madrasah Aliyah has not been optimally implemented and falls into the less than satisfactory category. Therefore, the most effective solution for the inadequate implementation of the guidance and counseling program at this school is for the principal to hold meetings with the counselor and subject teachers regarding the implementation of the counseling program at the school and the challenges faced. It is anticipated that following this meeting, the implementation of counseling at the public madrasah aliyah will be well-coordinated and function as intended